Barrier-free mobility assessment of General Luna Street, Intramuros, Manila - Arce, Carmina A. (Animo Repository, 2022)
The rise in motorization in the Philippines has led to the fall of most of its walkability ratings, leaving pedestrian and accessibility facilities behind. Despite the existence of the prevailing laws like the Accessibility Law or locally known as the Batas Pambansa 344 (BP 344), structures that lack proper access and mobility for persons with disabilities (PWDs) such as roads, crosswalks, crossings, government establishments, educational institutions, and historical sites are evident. Thus, this paper evaluates the facilities for PWDs in General Luna Street, Intramuros, Manila, where prominent heritage, cultural, educational and government agencies are located. An evaluation index was created in conducting the assessment of the facilities for accessibility based on the requirements set by the law. Upon examination, General Luna Street has a compliance rate of 19.72%. Results of the study found out that roads are subjected to sudden level changes and uneven surfaces, facilities like dropped curbs and handrails were missing, there were few allotted curb-cut outs, and obstructions that lessen the purpose of walkways. Six out of nine buildings in the study area have ramps in their entrances and the crossings that lack both tactile blocks and stop lines. Moreover, maps of the facilities were created, and an inventory was established with the application of geographic information system (GIS). An accessibility enhancement plan was provided to open prioritization opportunities and recommendations that could serve as a basis for development plans and for the inclusiveness of the society to PWD.